2010
DOI: 10.1517/17425250903427980
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferases: an overview in cancer research

Abstract: Although polygenic factors are involved in increased risk of cancer, the interindividual GST variability plays a central role in reduce cells exposure to carcinogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
163
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 108 publications
5
163
0
2
Order By: Relevance
“…2,[12][13][14] Body weight and body surface area have been also shown to contribute to PK variability. [15][16][17][18][19] Nevertheless, a large proportion of BU variability remains unexplained 20 and could be due to GST polymorphisms influencing GST activity [21][22][23][24][25] (Table 1). Although some studies have shown that GSTA1 genotypes influence the PK of oral and i.v.…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14] Body weight and body surface area have been also shown to contribute to PK variability. [15][16][17][18][19] Nevertheless, a large proportion of BU variability remains unexplained 20 and could be due to GST polymorphisms influencing GST activity [21][22][23][24][25] (Table 1). Although some studies have shown that GSTA1 genotypes influence the PK of oral and i.v.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Asians and Caucasians display higher frequencies of GSTM1-null genotypes than African populations (Di Pietro et al, 2010). The prevalence of the GSTT1-null genotype is low in Caucasians, and it is significantly greater in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with GSTT1 and GSTM1 genetic polymorphisms (Bartsch et al,1998;Liu et al, 2000;Duell et al, 2002;Jiao et al, 2007;Vrana et al, 2009;Jang et al, 2012), very few studies have studied GSTP1 genetic polymorphisms and their associations with pancreatic cancer risk. Only one previous study reported that GSTP1 polymorphisms were significantly associated with pancreatic cancer survival (Jiao et al, 2007) Because the frequencies of GST genotypes vary across populations and ethnicities (Di Pietro et al, 2010), large inter-individual differences might exist in the metabolic response to carcinogen exposure. As a result, the risk of pancreatic cancer could be partly determined by these factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that polymorphic expression of GSTs is associated with the altered xenobiotics detoxification efficiency, thus influencing an individual's susceptibility to carcinogens and various diseases (Di Pietro et al 2010;Suvakov et al 2013;Eslami and Sahebkar 2014;Kim et al 2015). Still, there are no data regarding the association between GST genetic polymorphism and bladder cancer risk, neither in patients with BEN, nor in individuals who originate from BEN regions.…”
Section: Introductionmentioning
confidence: 99%